2017
DOI: 10.1186/s13643-017-0529-0
|View full text |Cite
|
Sign up to set email alerts
|

Telephone consultations for general practice: a systematic review

Abstract: BackgroundThe use of information technology, including internet- and telephone-based resources, is becoming an alternative and supporting method of providing many forms of services in a healthcare and health management setting. Telephone consultations provide a promising alternative and supporting service for face-to-face general practice care. The aim of this review is to utilize a systematic review to collate evidence on the use of telephone consultation as an alternative to face-to-face general practice vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
1
22

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(152 citation statements)
references
References 12 publications
4
125
1
22
Order By: Relevance
“…The use of internet‐based resources provides many forms of services in a healthcare setting and improves accessibility, flexibility, efficiency and satisfaction; because barriers associated with healthcare access must be utilities, transportation, time, cost and limited availability of support providers. Evidence revealed that telephone consultations provide patient‐centered realistic care, support service for face‐to‐face appropriate medical care and reduce practice workload . To date, reports of telephone consultations in prenatal and postnatal health care are lacking in Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of internet‐based resources provides many forms of services in a healthcare setting and improves accessibility, flexibility, efficiency and satisfaction; because barriers associated with healthcare access must be utilities, transportation, time, cost and limited availability of support providers. Evidence revealed that telephone consultations provide patient‐centered realistic care, support service for face‐to‐face appropriate medical care and reduce practice workload . To date, reports of telephone consultations in prenatal and postnatal health care are lacking in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence revealed that telephone consultations provide patient-centered realistic care, support service for face-to-face appropriate medical care and reduce practice workload. 12 To date, reports of telephone consultations in prenatal and postnatal health care are lacking in Japan. From this point of view, planning for the prenatal and postnatal health care program began at Nara Medical University (NMU) in spring 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Telephone contact is used variably for assessment and triage of acute problems; [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] general practice consultations; [34][35][36][37][38][39][40] to offer health education; 41,42 and to offer support for those with chronic illness 43,44 or those in need of palliative care. 45 The literature on telephone consultations consists largely of small and heterogeneous primary studies, most of which had practical challenges or methodological flaws.…”
Section: Telephonementioning
confidence: 99%
“…También existe consenso en que deberá haber una reorganización de los tiempos de asistencia y búsqueda de métodos alternativos para evitar la presencia excesiva de enfermos y especialmente los neurológicos, ya que son especialmente vulnerables. Los encuestados prevén la potenciación de las consultas telefónicas que se han desarrollado ampliamente durante la pandemia (28,29 ) . Sin embargo, no parece que se generen cambios ni en la exploración clínica ni en las indicaciones de exploraciones complementarias, al menos por el especialista de Neurologia.…”
Section: Discussionunclassified